Business Intelligence & Analytics Cost Accounting: An Action Design Research Approach - Grytz, Raphael; Krohn-Grimberghe, Artus; Müller, Oliver (European Conference on Information Systems)
In order to sustain their competitive advantage, data driven organizations must continue investing in business intelligence and analytics (BI&A) while mitigating inherent cost increases. Research shows that examining outlays by individual BI&A artifact (e.g. reports, analytics) is necessary, but introduction in practice is cumbersome and adoption is slow. BI&A service-oriented cost allocation (BIASOCA) represents an improvement to this situation. This approach enables to render the BI&A cost pool accountable and improves cost transparency, which leads to a higher BI&A penetration of economically viable applications in organizations. Against this background, this paper aims at designing and implementing BIASOCA in a medium-sized company. To record organizational impact and increase customer acceptance, this study is carried out as action design research (ADR). Our findings indicate improvements in BI&A management from working with consumers to locate cost savings and drivers. After invoicing, consumers’ BI&A awareness increased, releasing resources while also making a better understanding of BIASOCA necessary. We detail how to implement BIASOCA in a real-life setting and the challenges attendant in so doing. Our research contributes to theory and practice with a set of design principles highlighting, besides the accuracy of cost accounting, the importance of collaboration, model comprehensibility and strategic alignment.

Trade and economic development: global causality and development- and openness-related heterogeneity - Gries, Thomas; Redlin, Margarete (International Economics and Economic Policy)

Forecasting IT Security Vulnerabilities - An Empirical Analysis - Yasasin, Emrah; Prester, Julian; Wagner, Gerit; Schryen, Guido (Computers & Security)
Today, organizations must deal with a plethora of IT security threats and to ensure smooth and uninterrupted business operations, firms are challenged to predict the volume of IT security vulnerabilities and allocate resources for fixing them. This challenge requires decision makers to assess which system or software packages are prone to vulnerabilities, how many post-release vulnerabilities can be expected to occur during a certain period of time, and what impact exploits might have. Substantial research has been dedicated to techniques that analyze source code and detect security vulnerabilities. However, only limited research has focused on forecasting security vulnerabilities that are detected and reported after the release of software. To address this shortcoming, we apply established methodologies which are capable of forecasting events exhibiting specific time series characteristics of security vulnerabilities, i.e., rareness of occurrence, volatility, non-stationarity, and seasonality. Based on a dataset taken from the National Vulnerability Database (NVD), we use the Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) to measure the forecasting accuracy of single, double, and triple exponential smoothing methodologies, Croston's methodology, ARIMA, and a neural network-based approach. We analyze the impact of the applied forecasting methodology on the prediction accuracy with regard to its robustness along the dimensions of the examined system and software package "operating systems", "browsers" and "office solutions" and the applied metrics. To the best of our knowledge, this study is the first to analyze the effect of forecasting methodologies and to apply metrics that are suitable in this context. Our results show that the optimal forecasting methodology depends on the software or system package, as some methodologies perform poorly in the context of IT security vulnerabilities, that absolute metrics can cover the actual prediction error precisely, and that the prediction accuracy is robust within the two applied forecasting-error metrics.

Integration of Novel Sensors and Machine Learning for Predictive Maintenance in Medium Voltage Switchgear to Enable the Energy and Mobility Revolutions - Hoffmann, Martin W.; Wildermuth, Stephan; Gitzel, Ralf; Boyaci, Aydin; Gebhardt, Jörg; Kaul, Holger; Amihai, Ido; Forg, Bodo; Suriyah, Michael; Leibfried, Thomas; Stich, Volker; Hicking, Jan; et al. (Sensors)
The development of renewable energies and smart mobility has profoundly impacted the future of the distribution grid. An increasing bidirectional energy flow stresses the assets of the distribution grid, especially medium voltage switchgear. This calls for improved maintenance strategies to prevent critical failures. Predictive maintenance, a maintenance strategy relying on current condition data of assets, serves as a guideline. Novel sensors covering thermal, mechanical, and partial discharge aspects of switchgear, enable continuous condition monitoring of some of the most critical assets of the distribution grid. Combined with machine learning algorithms, the demands put on the distribution grid by the energy and mobility revolutions can be handled. In this paper, we review the current state-of-the-art of all aspects of condition monitoring for medium voltage switchgear. Furthermore, we present an approach to develop a predictive maintenance system based on novel sensors and machine learning. We show how the existing medium voltage grid infrastructure can adapt these new needs on an economic scale.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Inszenierungen im digitalen Bild. Eine Rekonstruktion der Selfie-Praktiken Jugendlicher mittels der Dokumentarischen Bildinterpretation. - Schwabl, Franziska

Fotografien als Zugang zur Lebenswelt Jugendlicher. Eine Analyse der digitalen Inszenierungspraktiken Jugendlicher im berufsschulischen Übergangssystem. - Schwabl, Franziska (bwp@Berufs-und Wirtschaftspädagogik – online)

Against All Odds: Tentative Steps Toward Efficient Information Sharing in Groups - Schlangenotto, Darius; Schnedler, Wendelin; Vadovic, Radovan (Games)

Revisiting a Remedy Against Chains of Unkindness - Schnedler, Wendelin; Stephan, Nina Lucia (Schmalenbach Business Review)

Extending Loyalty Programs with BI Functionalities A Case Study for Brick-and-Mortar Stores - Kucklick, Jan-Peter; Kamm, Michael Reiner; Schneider, Johannes; vom Brocke, Jan (Proceedings of the 53rd Hawaii International Conference on System Sciences)
Effective customer loyalty programs are essential for every company. Small and medium sized brick-and- mortar stores, such as bakeries, butcher and flower shops, often share a common overarching loyalty program, organized by a third-party provider. Furthermore, these small shops have limited resources and often cannot afford complex BI tools. Out of these reasons we investigated how traditional brick-and- mortar stores can benefit from an expansion of service functionalities of a loyalty card provider. To answer this question, we cooperated with a cross-industry customer loyalty program in a polycentric region. The loyalty program was transformed from simple card-based solution to a mobile app for customers and a web- application for shop owners. The new solution offers additional BI services for performing data analytics and strengthening the position of brick-and-mortar stores. Participating shops can work together in order to increase sales and align marketing campaigns. Therefore, shopping data from 12 years, 55 shops, and 19,000 customers was analyzed.
Keywords: brick-and-mortar stores; business intelligence; case study; loyalty program

Data mining for small shops: Empowering brick-and-mortar stores through BI functionalities of a loyalty program1 - Kamm, Michael Reiner; Kucklick, Jan-Peter; Schneider, Johannes; vom Brocke, Jan (Information Systems Management)
While the analysis and usage of data are increasing in importance, the application of sophisticated BI solutions in small stores is limited by available technical capabilities and financial resources. This study investigates how brick-and-mortar stores can benefit from an expansion of service functionalities of a cross-industry loyalty card provider. Digitalizing the loyalty program created new opportunities, while the analysis of shopping data of 13 years, 19,000 customers, and 55 shops empowered data-based decision support.
Keywords: Customer loyalty; case study; brick-and-mortar stores; business intelligence; loyalty programs

Information Design in Coordination Games with Risk Dominant Equilibrium Selection - Ebert, Michael; Kadane, Joseph (Jay) B.; Simons, Dirk; Stecher, Jack Douglas

Kapazitätsplanung im Rahmen eines strategischen Kooperationsmanagements - Betz, Stefan (Neuere Entwicklungen in Produktion und Controlling)

Zieloptimale Anzahl von Partnern in Beschaffungskollaborationen - Osthoff, Lennart (Neuere Entwicklungen in Produktion und Controlling)

Zieloptimale Variantenvielfalt in der Produktionsplanung - Betz, Stefan (Neuere Entwicklungen in Produktion und Controlling)

Neuere Entwicklungen in Produktion und Controlling

Produktionsprogrammplanung bei variierender Fertigungstiefe - Plückebaum, Daniel (Neuere Entwicklungen in Produktion und Controlling)

Eignung ausgewählter Entscheidungsunterstützungsinstrumente für die Planung, Steuerung und Kontrolle von Produktinnovationen - Heidmann , Mathis (Neuere Entwicklungen in Produktion und Controlling)

Kollaborationsentscheidungen im Supply Chain Management - Osthoff, Lennart

Marktmissbrauch in digitalen Märkten - eine wettbewerbspolitische Analyse mit Fallbeispielen von Google, Facebook und Amazon - Niggemeyer, Laura

Challenges for Competition Policy in Data-Driven Mergers - Schlegel, Manuela

Marktmissbrauch in digitalen Märkten - Eine wettbewerbspolitische Analyse am Beispiel von Facebook - Neibert, Katharina

Zu den volkswirtschaftlichen Auswirkungen von Marktmacht am Fallbeispiel der Walt Disney Company - Naseri, Gitti

Preisdifferenzierung im Online-Handel am Beispiel Amazon und Obi - Laudage, Felix

Zuordnung und Anreizkompatibilität - Eine experimentelle Untersuchung - Posmetni, Lena

Auswirkungen der Preisdiskriminierung im Online Handel - Eine Wohlfahrtsanalyse am Beispiel von Amazon - Hensel, Jason

Zur Effizienzsteigerung durch Reputationsmechanismen auf digitalen Märkten - Multani, Manjinder Singh

Information asymmetry and the SEC framework in digital markets - On the role of reputation systems in alleviating buyers' skepticism and inducing their willingness to pay - Bellouchi, Houda

Auswirkungen der digitalen Flexibilisierung des Fertigungsortes auf die Verteilung der Besteuerungsrechte – Ergebnisse von Modellrechnungen zum 3D-Druck-Verfahren - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren (Steuer und Wirtschaft)

COVID-19 and investor behavior - Ortmann, Regina; Pelster, Matthias; Wengerek, Sascha Tobias (Finance Research Letters)
Keywords: Finance

Zuordnungsverfahren für Tauschbörsen - N., N.

Weitsichtigkeit zur Bildung stabiler Koalitionen - eine spieltheoretische Analyse - N., N.

Verhandeltes strategisches Verhalten - N., N.

Kronzeugenprogramme zur Aufdeckung von Kartellen - Eine spieltheoretische Analyse - N., N.

Eine ökonomische Analyse der Piraterie in zweiseitigen Softwaremärkten - N., N.

Kulturelle Unterschiede beim Lösen von Verhandlungsproblemen - N., N.

Productivity optimization through project matching - N., N.

Matching Mechanisms and Organ Exchange - N., N.

Cartel Fines in the European Union - N., N.

Anspruchsregeln in Verhandlungen - N., N.

Die Zusammenstellung eines Sortiments als Beispiel interdependenter Verhandlungen - N., N.

Matching in Netzwerken - N., N.

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar A.; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Prudence and prevention: Empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik
Theoretical papers show that optimal prevention decisions in the sense of selfprotection (i.e., primary prevention) depend not only on the level of (second-order) risk aversion but also on higher-order risk preferences such as prudence (third-order risk aversion). We study empirically whether these theoretical results hold and whether prudent individuals show less preventive (self-protection) effort than non-prudent individuals. We use a unique dataset that combines data on higher-order risk preferences and various measures of observed real-world prevention behavior. We find that prudent individuals indeed invest less in self-protection as measured by influenza vaccination. This result is driven by high risk individuals such as individuals >60 years of age or chronically ill. We do not find a clear empirical relationship between riskpreferences and prevention in the sense of self-insurance (i.e. secondary prevention). Neither risk aversion nor prudence is related to cancer screenings such as mammograms, Pap smears or X-rays of the lung.
Keywords: prudence; risk preferences; prevention; vaccination; screening

Do product testing programs lead to more favorable online reviews? (ausgezeichnet mit Best Paper Award) - Garnefeld, I.; Krah, T.; Böhm, Eva; Gremler, D. D. (2020 AMA Winter Academic Conference, San Diego, CA)

Manufacturers’ service growth through mergers and acquisitions – An event study - Eggert, A.; Böhm, Eva; Akalan, R.; Gebauer, H. (2020 AMA Winter Academic Conference, San Diego, CA)

Drivers and outcomes of salespersons’ value opportunity recognition competence in solution selling - Böhm, Eva; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang; Haas, Alexander (Journal of Personal Selling and Sales Management)
Keywords: Management of Technology and Innovation; Human Factors and Ergonomics

Political embeddedness and firms’ choices of earnings management strategies in China - Wang, Zhi; Braam, Geert; Reimsbach, Daniel; Wang, Jiaxin (Accounting & Finance)
Abstract We examine whether and how political embeddedness influences financial reporting quality in China by investigating how government ownership and political connections affect Chinese listed firms’ choices of earnings management strategies. The results show that state‐owned enterprises (SOEs), and in particular, central SOEs, are more likely to substitute accrual‐based earnings management strategies with costlier but less detectable real earnings management strategies than non‐SOEs. The results also indicate that politically connected enterprises (PCEs) are more likely to employ less detectable real earnings management strategies than non‐PCEs, so much so that PCEs’ total earnings management level is higher than that of non‐PCEs.
Keywords: Economics; Econometrics and Finance (miscellaneous); Finance; Accounting

Bringing Signaling Theory to Intermediated Voluntary Disclosure. Commentary on “Detecting False Accounts in Intermediated Voluntary Disclosure” by Patrick Callery and Jessica Perkins - Hahn, Rüdiger; Reimsbach, Daniel (Academy of Management Discoveries)

Corporate Entrepreneurship: Die Rolle und Bedeutung des Humankapitals - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

Corporate Entrepreneurship durch die Allokation von Ressourcen - Megow, N.; Kabst, Rüdiger (Perspektiven des Entrepreneurships: Unternehmerische Konzepte zwischen Theorie und Praxis)